Seroprevalence of herpes simplex virus type 1 and type 2 among the migrant workers in Qatar - Gheyath K. Nasrallah (9200525) (2023)
Background Limited data exists on herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) infections in migrant populations. This study investigated HSV-1 and HSV-2 seroprevalences and associations among craft and manual workers (CMWs) in Qatar who constitute 60% of Qatar’s population. Methods A national population-based cross-sectional seroprevalence survey was conducted on the CMW population, all men, between July 26 and September 9, 2020. 2,612 sera were tested for anti-HSV-1 IgG antibodies using HerpeSelect 1 ELISA IgG kits and for anti-HSV-2 IgG antibodies using HerpeSelect 2 ELISA IgG kits (Focus Diagnostics, USA). Univariable and multivariable logistic regression analyses were conducted to identify associations with HSV-1 and HSV-2 infections. Results Serological testing identified 2,171 sera as positive, 403 as negative, and 38 as equivocal for HSV-1 antibodies, and 300 sera as positive, 2,250 as negative, and 62 as equivocal for HSV-2 antibodies. HSV-1 and HSV-2 seroprevalences among CMWs were estimated at 84.2% (95% CI 82.8–85.6%) and 11.4% (95% CI 10.1–12.6%), respectively. HSV-1 infection was associated with nationality, educational attainment, and occupation. HSV-2 infection was associated with age, nationality, and educational attainment. Conclusions Over 80% of CMWs are infected with HSV-1 and over 10% are infected with HSV-2. The findings highlight the need for sexual health programs to tackle sexually transmitted infections among the CMW population. Other Information Published in: Virology Journal License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12985-023-02157-1